Going to a concert - Rissman, Rebecca (Chicago [Ill.] Heinemann Library, 2012)
Discusses different types of concerts and the music that they feature, including operas, choral concerts, and marching band shows
A gift from book Africa
Arts
1 2 11 13
Keywords: Concerts -- Juvenile literature; School field trips -- Juvenile literature; School field trips